(untitled) (Tanzania Medical Journal, 2008)
Background: Observations made in golden hamster Harderian gland have shown that the female glands contained a higher numerical density of the myoepithelial cells compared to those in the male glands. The findings were based on a single report and did not indicate clearly the part of the gland that was examined. Broad Objective: To study the morphology of the myoepithelial cells and the basal surfaces of the glandular cells in the small and large lobes of the Harderian gland. Study Setting and Methodology: The study used the scanning electron and lesser confocal microscopes to observe the Harderian gland of the golden hamster. Results: The morphology of the myoepithelial cells of the large lobes both in male and female glands appeared to be similar. The myoepithelial cells of the small lobes from both male and female glands also appeared to be similar but unlike those in the large lobes contained broader cytoplasmic processes Conclusions: The morphology of the myoepithelial cells in the male and female glands does not show sexual differences an indication that these cells may be not sexually regulated. The findings open way for future research towards the understanding of the myoepithelial cell physiology in the Harderian gland of the golden hamster. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 23-29